Metabolic profile of nicotine in subjects whose CYP2A6 gene is deleted - Yamanaka, Hiroyuki; Nakajima, Miki; Nishimura, Kiyoko; Yoshida, Ryoko; Fukami, Tatsuki; Katoh, Miki; Yokoi, Tsuyoshi (European journal of pharmaceutical sciences, 2004)
Generally, 70–80% of absorbed nicotine is mainly metabolized to cotinine by cytochrome P450 (CYP) 2A6. There is genetic polymorphism in the human CYP2A6 gene. Among several mutated alleles, CYP2A6*4 allele is a whole deleted type. The purpose of the present study was to clarify the metabolic profile of nicotine in subjects whose CYP2A6 gene is deleted. We developed a liquid chromatography–tandem mass spectrometry (LC–MS/MS) method for nicotine and its nine metabolites. Excretion levels of nicotine and its metabolites in 24 h accumulated urine after the chewing of one piece of nicotine gum were evaluated in five Japanese subjects whose CYP2A6 genotype was determined. In three subjects with CYP2A6*1A/ CYP2A6*1A, CYP2A6*1A/ CYP2A6*1B, and CYP2A6*1A/ CYP2A6*4 (group I), nicotine was mainly excreted as cotinine, trans-3′-hydroxycotinine, and their glucuronide (approximately 60%). In contrast, in two subjects with CYP2A6*4/ CYP2A6*4 (group II), trace levels of cotinine, cotinine N-glucuronide, and cotinine 1′- N-oxide were detected. Trans-3′-hydroxycotinine and its O-glucuronide were not detected. The excretion levels of nicotine itself, nicotine N-glucuronide, and nicotine 1′- N-oxide were higher than those in the other three subjects. The total excretion levels of these three compounds were approximately 95% in group II versus 35% in group I. However, the sum of the excretion levels of nicotine and all metabolites was similar among these five subjects. This is the first report of the metabolic profile of nicotine in subjects whose CYP2A6 gene is deleted.